POLA KOMUNIKASI ORGANISASI RADIO AMATIR INDONESIA (ORARI) DI KECAMATAN TINGGIMONCONG KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The subject matter of this research is: How is the pattern of communication between the Indonesian radio amateur organization in Tinggimoncong District, Gowa Regency? The subject matter is divided into several submas problems, namely: 1) How is the pattern of communication of the Indonesian Radio Amateur Organization (ORARI) which plays an important role in increasing the flow of communication between members?, and 2) The role of the Indonesian Radio Amateur Communication Media (ORARI) in conveying information to the public? This research is qualitative and uses a communication approach. The research data source came from the Chair and Members of the Indonesian Radio Amateur Organization (ORARI) in Tinggimoncong District, Gowa Regency. Data collection methods include observations, interviews, documentation, and reference searches. Then, data processing and analysis techniques are carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the ORARI Communication Patterns of the Tinggimoncong District in increasing the flow of communication between members were: primary communication patterns and secondary communication patterns. While the role of the communication media used by ORARI to convey information to the community: Very effective and use Handy Talky (HT) communication media and radio rigging communication media (radio rigging). The implications of this study are: It is expected to provide benefits and add insight into how communication patterns can affect the flow of information communication and coordination in an organization. It is expected to increase understanding of the effectiveness of communication media, enriching understanding of how certain media affect recipients and understanding of information by the community.